"Does The Water Repeat?": Reading Caribbean-South African Contemporary Fiction. Issue 3 (3rd April 2022) - Collis-Buthelezi, Victoria J.
Abstract : This essay offers a reading of Maryse Condé's The Story of the Cannibal Woman (2003) and Yewande Omotoso's The Woman Next Door (2016). I argue that these contemporary imaginings of Black women's Caribbean-South Africa travel disrupt our notions of literary categorization and the nation through productions of waterborne selves and community. Ultimately, I explore the ways in which the texts themselves push against land-based notions of Black being and belonging towards articulating transnational Black women's unique roles in sea histories of commodification and capital.